Question Number 104062 by bramlex last updated on 19/Jul/20
$$\begin{cases}{\frac{{x}}{{y}}\:+\:\frac{{y}}{{x}}\:=\:\frac{\mathrm{13}}{\mathrm{6}}}\\{{x}+{y}\:=\:\mathrm{5}}\end{cases} \\ $$$${find}\:{the}\:{solution} \\ $$
Commented by Rasheed.Sindhi last updated on 19/Jul/20
$${An}\:{Other}\:{Way}\:_{\searrow} ^{\nearrow} \:\: \\ $$$$\frac{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} }{{xy}}=\frac{\mathrm{13}}{\mathrm{6}} \\ $$$$\mathrm{6}{x}^{\mathrm{2}} −\mathrm{13}{xy}+\mathrm{6}{y}^{\mathrm{2}} =\mathrm{0} \\ $$$$\left(\mathrm{3}{x}−\mathrm{2}{y}\right)\left(\mathrm{2}{x}−\mathrm{3}{y}\right)=\mathrm{0} \\ $$$$\left(\begin{cases}{\mathrm{3}{x}−\mathrm{2}{y}=\mathrm{0}}\\{{x}+{y}=\mathrm{5}}\end{cases}\:\right)\vee\:\left(\begin{cases}{\mathrm{2}{x}−\mathrm{3}{y}=\mathrm{0}}\\{{x}+{y}=\mathrm{5}}\end{cases}\right) \\ $$$$\mathrm{3}{x}−\mathrm{2}\left(\mathrm{5}−{x}\right)=\mathrm{0}\:\vee\:\mathrm{2}{x}−\mathrm{3}\left(\mathrm{5}−{x}\right)=\mathrm{0} \\ $$$${x}=\mathrm{2},{y}=\mathrm{3}\:\:\:\:\:\:\:\:\vee\:\:\:{x}=\mathrm{3},{y}=\mathrm{2} \\ $$
Commented by bemath last updated on 19/Jul/20
$${cooll} \\ $$
Commented by bramlex last updated on 19/Jul/20
$${thank}\:{you}\:{all}\: \\ $$
Commented by Dwaipayan Shikari last updated on 19/Jul/20
$$\mathrm{Another}\:\mathrm{way} \\ $$$$\frac{\mathrm{x}}{\mathrm{y}}+\mathrm{1}=\frac{\mathrm{5}}{\mathrm{y}}\Rightarrow\frac{\mathrm{x}}{\mathrm{y}}=\frac{\mathrm{5}}{\mathrm{y}}−\mathrm{1}\:\:\:\mathrm{and}\:\:\:\frac{\mathrm{y}}{\mathrm{x}}=\left(\frac{\mathrm{5}}{\mathrm{y}}−\mathrm{1}\right)^{−\mathrm{1}} \\ $$$$\frac{\mathrm{x}}{\mathrm{y}}+\frac{\mathrm{y}}{\mathrm{x}}=\frac{\mathrm{13}}{\mathrm{6}} \\ $$$$\frac{\mathrm{5}−\mathrm{y}}{\mathrm{y}}+\frac{\mathrm{y}}{\mathrm{5}−\mathrm{y}}=\frac{\mathrm{13}}{\mathrm{6}}\Rightarrow\frac{\mathrm{25}+\mathrm{2y}^{\mathrm{2}} −\mathrm{10y}}{\mathrm{5y}−\mathrm{y}^{\mathrm{2}} }=\frac{\mathrm{13}}{\mathrm{6}} \\ $$$$\frac{\mathrm{25}+\mathrm{2y}^{\mathrm{2}} −\mathrm{10y}}{\mathrm{10y}−\mathrm{2y}^{\mathrm{2}} }+\mathrm{1}=\frac{\mathrm{13}}{\mathrm{12}}+\mathrm{1}\Rightarrow\frac{\mathrm{25}}{\mathrm{10y}−\mathrm{2y}^{\mathrm{2}} }=\frac{\mathrm{25}}{\mathrm{12}}\Rightarrow\mathrm{2y}^{\mathrm{2}} −\mathrm{10y}+\mathrm{12}=\mathrm{0}\rightarrow\left(\mathrm{a}\right) \\ $$$$\:\:\:\:\:\:\mathrm{So}\:\:\:\:\mathrm{y}=\mathrm{3},\mathrm{2}\:\:\left(\mathrm{from}\left(\mathrm{a}\right)\right) \\ $$$$\frac{\mathrm{x}}{\mathrm{3}}+\mathrm{1}=\frac{\mathrm{5}}{\mathrm{3}}\:\:\:\:\mathrm{or}\:\frac{\mathrm{x}}{\mathrm{2}}+\mathrm{1}=\frac{\mathrm{5}}{\mathrm{2}} \\ $$$$\mathrm{x}=\mathrm{2}\:\mathrm{or}\:\mathrm{3} \\ $$$$\begin{cases}{\mathrm{x}=\mathrm{2},\mathrm{3}}\\{\mathrm{y}=\mathrm{3},\mathrm{2}}\end{cases} \\ $$$$ \\ $$$$ \\ $$
Answered by Dwaipayan Shikari last updated on 19/Jul/20
$$\frac{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} }{\mathrm{2}{xy}}=\frac{\mathrm{13}}{\mathrm{12}} \\ $$$$\frac{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} +\mathrm{2}{xy}}{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} −\mathrm{2}{xy}}=\frac{\mathrm{25}}{\mathrm{1}} \\ $$$$\left(\frac{{x}+{y}}{{x}−{y}}\right)^{\mathrm{2}} =\frac{\mathrm{25}}{\mathrm{1}} \\ $$$$\frac{\mathrm{25}}{\left({x}−{y}\right)^{\mathrm{2}} }=\frac{\mathrm{25}}{\mathrm{1}} \\ $$$${x}−{y}=\mathrm{1}\:\:\:\:{or}\:\:{y}−{x}=\mathrm{1} \\ $$$${x}+{y}=\mathrm{5} \\ $$$$\begin{cases}{{x}=\mathrm{3},\mathrm{2}\:\:\:\:\:\:\:\:}\\{{y}=\mathrm{2},\mathrm{3}}\end{cases} \\ $$
Commented by Rasheed.Sindhi last updated on 19/Jul/20
$$\mathcal{E}{verybody}\:{is}\:{not}\:{as}\:{intelligent} \\ $$$$\left.{as}\:{you}\:{are}!\::\right) \\ $$$$\mathcal{S}{o}\:{pl}\:{insert}\:{some}\:{steps}\:{between} \\ $$$$\mathrm{1}{st}\:\&\:\mathrm{2}{nd}\:{lines}. \\ $$
Commented by Dwaipayan Shikari last updated on 19/Jul/20
$${Sorry}\:{sir}\:{for}\:{your}\:{inconvenience} \\ $$
Commented by Rasheed.Sindhi last updated on 19/Jul/20
$$\frac{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} +\mathrm{2}{xy}}{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} −\mathrm{2}{xy}}=\frac{\mathrm{13}+\mathrm{12}}{\mathrm{13}−\mathrm{12}} \\ $$$$\mathcal{T}{his}\:{was}\:{necessary}\:{step}\:{to} \\ $$$${insert}.\mathcal{W}{ithout}\:{this}\:{the}\:{answer} \\ $$$${seemed}\:{a}\:{riddle}! \\ $$$${Pl}\:{don}'{t}\:{mind}! \\ $$
Commented by Rasheed.Sindhi last updated on 19/Jul/20
$$\mathcal{N}{ice}\:\mathcal{S}{olution}! \\ $$
Commented by 1549442205PVT last updated on 19/Jul/20
$$\mathrm{applying}\:\mathrm{the}\:\mathrm{property}:\:\frac{\mathrm{a}}{\mathrm{m}}=\frac{\mathrm{b}}{\mathrm{n}}=\frac{\mathrm{a}+\mathrm{b}}{\mathrm{m}+\mathrm{n}}=\frac{\mathrm{a}−\mathrm{b}}{\mathrm{m}−\mathrm{n}} \\ $$$$\frac{\mathrm{x}^{\mathrm{2}} +\mathrm{y}^{\mathrm{2}} }{\mathrm{13}}=\frac{\mathrm{2xy}}{\mathrm{12}}=\frac{\mathrm{x}^{\mathrm{2}} +\mathrm{y}^{\mathrm{2}} +\mathrm{2xy}}{\mathrm{25}}=\frac{\mathrm{x}^{\mathrm{2}} +\mathrm{y}^{\mathrm{2}} −\mathrm{2xy}}{\mathrm{1}} \\ $$$$\Rightarrow\frac{\mathrm{x}^{\mathrm{2}} +\mathrm{2xy}+\mathrm{y}^{\mathrm{2}} }{\mathrm{x}^{\mathrm{2}} −\mathrm{2xy}+\mathrm{y}^{\mathrm{2}} }=\frac{\mathrm{25}}{\mathrm{1}} \\ $$
Answered by bobhans last updated on 19/Jul/20
$${set}\:{x}+{y}\:=\:{u}\:,\:{xy}\:=\:{v}\: \\ $$$$\frac{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} }{{xy}}\:=\:\frac{\mathrm{13}}{\mathrm{6}}\:\Rightarrow\frac{\left({x}+{y}\right)^{\mathrm{2}} −\mathrm{2}{xy}}{{xy}}\:=\:\frac{\mathrm{13}}{\mathrm{6}} \\ $$$$\mathrm{25}−\mathrm{2}{v}\:=\:\frac{\mathrm{13}{v}}{\mathrm{6}}\:\Rightarrow\mathrm{150}\:=\:\mathrm{25}{v}\: \\ $$$$\begin{cases}{{v}\:=\:\mathrm{6}\rightarrow{y}\:=\:\frac{\mathrm{6}}{{x}}}\\{{u}=\mathrm{5}\rightarrow\:{x}+\frac{\mathrm{6}}{{x}}\:=\:\mathrm{5}\:;\:{x}^{\mathrm{2}} −\mathrm{5}{x}+\mathrm{6}=\mathrm{0}}\end{cases} \\ $$$$\begin{cases}{{x}=\:\mathrm{3}\rightarrow{y}=\:\mathrm{2}}\\{{x}\:=\:\mathrm{2}\rightarrow{y}=\mathrm{3}}\end{cases}\:{solution}\:{set}\:\left\{\left(\mathrm{3},\mathrm{2}\right);\left(\mathrm{2},\mathrm{3}\right)\right\} \\ $$
Answered by Rasheed.Sindhi last updated on 19/Jul/20
$$\mathrm{Using}\:\mathrm{formula}: \\ $$$$\underset{−} {\:\:\:\:\:\:\:\left({x}+{y}\right)^{\mathrm{2}} −\left({x}−{y}\right)^{\mathrm{2}} =\mathrm{4}{xy}\:\:\:\:\:\:\:\:\:} \\ $$$$\begin{cases}{\frac{{x}}{{y}}\:+\:\frac{{y}}{{x}}\:=\:\frac{\mathrm{13}}{\mathrm{6}}…..\left({i}\right)}\\{{x}+{y}\:=\:\mathrm{5}…………..\left({ii}\right)}\end{cases}\:\:\:\:\:\:\:\: \\ $$$$\left({i}\right)\Rightarrow\frac{{x}}{{y}}\:+\mathrm{1}+\:\frac{{y}}{{x}}+\mathrm{1}\:=\:\frac{\mathrm{13}}{\mathrm{6}}+\mathrm{2} \\ $$$$\:\:\:\:\:\frac{{x}+{y}}{{y}}\:+\:\frac{{x}+{y}}{{x}}\:=\frac{\mathrm{25}}{\mathrm{6}} \\ $$$$\:\:\:\:\:\frac{\mathrm{5}}{{y}}\:+\:\frac{\mathrm{5}}{{x}}\:=\frac{\mathrm{25}}{\mathrm{6}} \\ $$$$\:\:\:\:\:\frac{\mathrm{1}}{{y}}\:+\:\frac{\mathrm{1}}{{x}}\:=\frac{\mathrm{5}}{\mathrm{6}}…………….\left({iii}\right) \\ $$$$\left({ii}\right)\Rightarrow\frac{{x}}{{xy}}+\frac{{y}}{{xy}}=\frac{\mathrm{5}}{{xy}} \\ $$$$\:\:\:\:\:\:\:\:\:\:\: \\ $$$$\:\:\:\:\:\:\:\frac{\mathrm{1}}{{y}}\:+\:\frac{\mathrm{1}}{{x}}=\mathrm{5}\left(\frac{\mathrm{1}}{{x}}\right)\left(\frac{\mathrm{1}}{{y}}\right)…….\left({iv}\right) \\ $$$$\left({iii}\right)\:\&\:\left({iv}\right): \\ $$$$\:\:\:\:\:\:\:\:\:\left(\frac{\mathrm{1}}{{x}}\right)\left(\frac{\mathrm{1}}{{y}}\right)=\frac{\mathrm{1}}{\mathrm{6}}\Rightarrow{xy}=\mathrm{6} \\ $$$${x}+{y}=\mathrm{5}\:\wedge\:{xy}=\mathrm{6} \\ $$$$\:\:\:\:\left({x}+{y}\right)^{\mathrm{2}} −\left({x}−{y}\right)^{\mathrm{2}} =\mathrm{4}{xy} \\ $$$$\:\:\:\:\:\left(\mathrm{5}\right)^{\mathrm{2}} −\left({x}−{y}\right)^{\mathrm{2}} =\mathrm{4}\left(\mathrm{6}\right) \\ $$$$\:\:\:\:\:\:\:\:{x}−{y}=\pm\mathrm{1} \\ $$$$\begin{cases}{{x}+{y}=\mathrm{5}}\\{{x}−{y}=\mathrm{1}\:\:}\end{cases}\:\:\:\:\vee\:\:\:\begin{cases}{{x}+{y}=\mathrm{5}}\\{{x}−{y}=−\mathrm{1}}\end{cases} \\ $$$${x}=\mathrm{3},{y}=\mathrm{2}\:\:\:\:\:\:\vee\:\:\:{x}=\mathrm{2},{y}=\mathrm{3} \\ $$